2008
DOI: 10.1158/1055-9965.epi-07-0559
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mammographic Density with the Pathology of Subsequent Breast Cancer among Postmenopausal Women

Abstract: Background: Limited studies have examined the associations between mammographic density and subsequent breast tumor characteristics. Methods: Eligible women were part of a case-control study of postmenopausal breast cancer, were 40 years or older and had a routine mammogram 4 years or more before their diagnosis. Mammographic density (percent density, dense area, and nondense area) was estimated using a computer-assisted thresholding program. At the time of cancer diagnosis, cases were classified as asymptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 24 publications
5
37
3
Order By: Relevance
“…It was reported that ER-positive compared to negative tumours were more frequently associated with dense breast tissue. By contrast, breast tissue density was not associated with the expression of ER in the present study, which is consistent with the findings of with Ghosh et al (22). This study reported that the overexpression of IGF-1R may be significantly associated with dense breast tissue on mammography.…”
Section: Os Dfs -----------------------------------------------------supporting
confidence: 93%
See 1 more Smart Citation
“…It was reported that ER-positive compared to negative tumours were more frequently associated with dense breast tissue. By contrast, breast tissue density was not associated with the expression of ER in the present study, which is consistent with the findings of with Ghosh et al (22). This study reported that the overexpression of IGF-1R may be significantly associated with dense breast tissue on mammography.…”
Section: Os Dfs -----------------------------------------------------supporting
confidence: 93%
“…terms of intra-and inter-observer variability. According to comparative studies on different mammographic readings, no significant difference was found between the BI-RADS-based group and the other group using computer-based calculation of absolute areas in terms of several clinicopathological factors (21,22). In view of mammographic timing, screening at a certain point in time during the menstrual cycle possibly ensures a more accurate measurement of density; however, in the majority of the cases, density does not vary significantly depending on different points of time during the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%
“…4,[94][95][96][97][98][99][100] Women with high breast density have been reported to have a four to six times increased risk of developing breast cancer compared with those with low breast density, 95,[101][102][103][104][105] and high breast density has also been linked to an increased risk of cancers not detected at screening, 4,8,96,106,107 larger tumour size [108][109][110] and positive lymph nodes. 109,[111][112][113] The underlying cause of these links are thought to be numerous, and early studies hypothesised that a significant reason for an increase in breast cancer incidence with higher density breasts was as a result of a 'masking bias' that made mammographic screening less sensitive to cancer detection.…”
Section: Introductionmentioning
confidence: 99%
“…Whether density only is related to risk of breast cancer or it also influences tumor subtype remains to be clarified. Previous published studies on the relationship between MD and tumor characteristics are highly inconsistent [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%